Radar observations of tropical cyclones over the Indian Seas - RAGHAVAN, S. (MAUSAM, 1997)
ABSTRACT. A review is presented of the radar observation of tropical cyclones in the Indian seas. The use of radar in operational cyclone tracking and forecasting as well as the knowledge gained from radar observations of the structure, wind and rainfall distribution and motion of cyclones are discussed. In the context of the expected introduction of operational Doppler ra1ars in India, the future prospects in the use of radar for operations and research are outlined. Some important areas where our understanding of cyclones can be improved by studies with radar in conjunction with other observations are listed.